Litter production and decomposition in a mixed araucaria forest in the south of Brazil - Caldato, Silvana L; Floss, Paulo A; Serafini Floss, Elzira C (Bosque (Valdivia), 2017)
The aim of the present work was to evaluate the litter production and decomposition in a mixed araucaria forest in the south of Brazil. The vegetation of the area is characterized by two forest types: forest type I, with the upper canopy dominated by Araucaria angustifolia; and forest type II, with higher diversity of tree species, predominantly broad-leafed species in the dominant canopy strata. To evaluate the litter production, 20 wood traps with 0.25 m2 of surface were installed. Ten samples of 0.25 m2 were monthly collected from the litter layer. Litter decomposition was evaluated from the instantaneous decay rate (K). The average of three years concluded that litter production did not differ significantly in the two types of forest studied: 7,661 kg ha–1 year–1 in forest type I and 8,624 kg ha–1 year–1 in forest type II. The months with the highest production in forest type II were correlated with periods of higher precipitation (spring and summer). The litter layer was significantly different for the two forest types, being heavier in forest type I with values of 9,924 kg ha–1 and 7,906 kg ha–1 for forest type II. The area with predominance of Araucaria angustifolia presented a slower rate of litter decomposition and nutrient release.